HUBUNGAN KEAKTIFAN IBU KE POSYANDU DENGAN STATUS GIZI BALITA DI KELURAHAN SUKANEGLA - Trisnawati, Cucu; Handayani , Sri (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background : Early detection of malnutrition can be done by monitoring the growth and development of children at the integrated health post. Toddlers who experience malnutrition can grow shorter, not gain weight, be underweight, and be less productive. prevalence based on the results of the 2018 Riskesdas in West Java: malnutrition 0.50%, undernutrition 1.72%, thin 2.81%, and never gain weight 2.41%; Objective : So we can find out how often mothers in Sukanegla District visit posyandu and this is related to the nutritional quality of their children. Method : This study uses a cross-sectional design. The sampling method is by using the Simple random sampling technique and the number of respondents is 88 respondents. Results : There were 54 respondents (61.4) mothers who actively attended posyandu and 34 respondents (38.6%) who did not actively attend posyandu. There were 18 under-nourished children (20.5%), 30 under-nourished children (34.1%), 33 under-nourished children (37.5%), and 7 under-nourished children (8.0%). research using the chi-square test obtained P Value = 0.027 with a significance level (α) of 0.05 so that there is a relationship between maternal activity in Posyandu and the nutritional status of toddlers. Conclusion : there is a relationship between mothers' activity at posyandu and the nutritional status of toddlers in Sukanegla Village in the Pasundan Community Health Center working area.